The antimalarial compound ELQ‐400 is an unusual inhibitor of the bc1 complex, targeting both Qo and Qi sites. Issue 8 (26th March 2018) - Song, Zehua; Iorga, Bogdan I.; Mounkoro, Pierre; Fisher, Nicholas; Meunier, Brigitte
Abstract : Inhibitors of the mitochondrial respiratory chain cytochrome bc 1 complex, such as the antimalarial atovaquone and ELQ‐300, and many well‐studied compounds, are classified as either Q o or Q i site inhibitors based on their site of action. Here, we investigated the site of action of ELQ‐400 that showed an unusual behaviour, being effective against parasites resistant to the Q o  site inhibitor atovaquone or to the Q i site inhibitor ELQ‐300. Analysis of yeast mutants and comparison with atovaquone and other ELQs strongly suggest that ELQ‐400 targets both Q o  and Q i  sites. Dual site inhibition would be particularly efficient as it would lower the risk of acquired resistance. However, such compounds are seldom found, which could be explained by structural and mechanistic differences between the sites. Abstract :